No Right to Family Life? Single Mothers and their Children in a “Mixed Economy of Welfare” in Switzerland, 1930s–1950s - Matter, Sonja (Historein, 2024)
In Switzerland single mothers, especially from the working class, were rarely able to support themselves and their children as a result of widespread discrimination against women in the labor market throughout the 20th century. Focusing on the case records of the social welfare of the city of Bern from the 1930s to 1950s, the article examines to what extent single mothers benefited from a ‘mixed economy of welfare’. The article points out that after the Second World War, social welfare measures were expanded with the introduction of widows’ and survivors’ insurance and the establishment of family allowances. While these new social insurance schemes undoubtedly brought improvements, the article shows that single mothers continued to experience practices of social exclusions. Especially, the combination of welfare dependency on the one hand, and guardianship measures on the other, often resulted in the out-of-home placement of the children of single mothers.